Adult-onset Still’s disease in pregnancy: case report and literature review - Liang Chao; Li Jia; Ke-Fang Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: Adult-onset Still’s disease (AOSD) is a clinical syndrome whose etiology and pathogenesis remain unclear. The clinical symptoms of AOSD mainly include fever, erythema, arthralgia and muscle pain, which cannot be diagnosed by specific auxiliary examination and can initially attack during pregnancy. The identification of the disease is revealed by a diagnosis of exclusion. Currently, the relationship between pregnancy and AOSD remains unclear. Here, we report on one case of AOSD during pregnancy that was admitted to the Beijing Anzhen Hospital affiliated to Capital Medical University. A 24-year-old woman was admitted to hospital due to intermittent fever, a history of pain and swelling of the large joints at 33 weeks gestation. After the diagnosis of AOSD, the symptoms relieved with medication. The patient delivered a premature, 3450 g baby successfully. Conclusions: The diagnostic criteria of pregnancy complicated by AOSD mainly depends on a diagnosis of exclusion. The literature both at home and abroad shows that the onset of AOSD is closely related to pregnancy, and that pregnancy is one of its predisposing factors. Its clinical manifestations are arthritis, arthromyalgia, fever, pharyngitis and so on, which involve multiple systems. There is no highly specific approach available in the laboratory examination and imaging for this disease.